Association between quality of life, physical activity, use of medication and costs of treatment for chronic diseases in Primary Care - Queiroz, Dayane C. [UNESP]; Turi, Bruna C. [UNESP]; Sarti, Flavia M.; Santos Ferro, Izabela dos [UNESP]; Morais, Luana C. de [UNESP]; Sanches Codogno, Jamile [UNESP] (Edizioni Minerva Medica, 2020)
BACKGROUND: The aim of this study was to investigate the costs and the health outcomes of primary care treatments for chronic diseases and to analyze the association between domains of quality of life (QoL), physical activity and healthcare costs. METHODS: The sample encompassed 292 patients aged 50 years or more in Brazilian primary care facilities, categorized in three groups: no drug treatment or only regular physical activity, only drug treatment, and drug treatment with regular physical activity. Patients were assessed in relation to quality of life, healthcare costs, regular physical activity, and use of medications. RESULTS: Results indicate higher cost-utility ratio among primary care patients adopting only drug treatment (3.92), followed by drug treatment with regular physical activity (3.21), and no drug treatment or only regular physical activity (0.12). CONCLUSIONS: QoL was significantly associated with risk factors for chronic diseases, especially obesity, and limitations in mobility showed important increases in healthcare costs. The dominant strategy in terms of cost-utility ratio was identified among primary care patients without drug treatment or physically active, followed by patients in drug treatment combined with regular physical activity. Drug treatment without regular physical activity showed worst results in relation to other primary care strategies.
Keywords: Cost-benefit analysis; Chronic diseases; Quality of life